The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/ijfs.15613
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic effect of petit‐high pressure carbon dioxide combined with cinnamon (Cinnamomum cassia) essential oil against Salmonella typhimurium

Abstract: Summary This work aimed to evaluate the synergistic effect of petit‐high pressure carbon dioxide (p‐HPCD) and cinnamon (Cinnamomum cassia) essential oil (CEO) against Salmonella typhimurium. The results showed synergetic antibacterial activity of p‐HPCD and CEO. After treatment with p‐HPCD and CEO with a final concentration of 0.03125% under 1.3 MPa at 30 °C for 5 h, the population of S. typhimurium was decreased by 6.22 log10 CFU/mL, significantly higher than p‐HPCD or CEO alone. The combined treatment induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 60 publications
(91 reference statements)
2
10
0
Order By: Relevance
“…In the experiments of this paper, the changes of ROS content were observed by measurement and fluorescence microscope. It was found that a large amount of ROS would be produced in Salmonella enteritidis cells treated with CEO, with the increase in CEO concentration indicating that CEO could induce bacterial cells to produce a large amount of ROS [ 52 ]. It also caused oxidative damage to cells, thereby playing a bacteriostatic effect [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the experiments of this paper, the changes of ROS content were observed by measurement and fluorescence microscope. It was found that a large amount of ROS would be produced in Salmonella enteritidis cells treated with CEO, with the increase in CEO concentration indicating that CEO could induce bacterial cells to produce a large amount of ROS [ 52 ]. It also caused oxidative damage to cells, thereby playing a bacteriostatic effect [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The minimum inhibitory concentration (MIC) of CIN against S. cerevisiae was obtained using a broth microdilution method [ 17 ]. The MIC indicated the lowest concentration of CIN that completely inhibited microbial growth after incubation for 24 h. In brief, the stock solution of CIN was first dissolved in Tween 80 at a ratio of 1:1 ( v / v ) and then mixed with the sterile YPD medium to prepare the CIN solutions with concentrations of 0.0025–0.04% ( v / v ).…”
Section: Methodsmentioning
confidence: 99%
“…The OST-200ML HPCO 2 system (Xi’an Oster Instrument Technology, Xi’an, China) was applied to inactivate S. cerevisiae . The pasteurization process, with CIN and p -HPCO 2 and the p -HPCO 2 setup, has been described in detail in our previous study [ 17 ]. The prepared yeast samples were transferred to the high-pressure vessel, which was placed in a thermostatic bath to control the process temperature.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations